EFFECT OF COMBRETUM INDICUM LEAF EXTRACT ON BLOOD SUGAR LEVELS AND PANCREAS HISTOLOGY OF ALLOXAN INDUCED MICE - Pertiwi, Anggita Endar; Aryani, Retno; Rosadi, Imam; Nugroho, Rudy Agung (Universitas Medan Area, 2024)
Diabetes is a health problem that affects more than half a billion people in the world. Several plants are known to have anti-diabetic activity, one of which is Dutch jasmine (Combretum indicum). This research was conducted to determine the effect of Combretum indicum leaf extract on blood sugar levels and histology of islets of Langerhans in mice. A total of 36 male mice aged 6-8 weeks were divided into 6 treatment groups, namely normal control (KN) without treatment; negative control (K) with alloxan treatment; positive control (K+) with alloxan and glibenclamide treatment; P1 treated with alloxan and Combretum indicum leaf extract at a dose of 100 mg/kgBW; P2 with treatment with alloxan and Combretum indicum leaf extract at a dose of 200 mg/kgBW; P3 with alloxan treatment and Combretum indicum leaf extract at a dose of 200 mg/kgBW. Mice that have been induced by alloxan will be treated with leaf extract and glibenclamide for 20 days. Blood sugar levels 3 days after alloxan induction were checked and checked again on the 10th and 20th days of treatment by taking blood through the blood vessels in the mice's tails and then measuring them using a glucometer. The pancreas was dissected on the 20th day and pancreatic histology preparations were made for histological analysis. The results of this study indicate that Combretum indicum leaf extract has antihyperglycemic effects by protecting islets of Langerhans cells from alloxan-induced oxidative stress.